Shifting vantage, common musings: the politics of Wordsworthian excursus in the poetry of Peter Riley. Issue 9 (21st October 2019) - Eltringham, Daniel
ABSTRACT: This article reads the poetry of Peter Riley in the tradition of the loco-descriptive excursion poem, interrogating the politics of its logic of ascent and return and the shifting vantage points it allows the twentieth- and twenty-first-century poet-traveller on the globalised world of capitalist 'gain'. It detects dual registers running throughout three excursive volumes – Noon Province (1989), The Llyn Writings (2007) and The Glacial Stairway (2011) – that turn around an ambivalent lexicon that is both spiritual and financial. The article shows how this duality maps onto the self-splitting of Romantic excursus in William Wordsworth and Jean-Jacques Rousseau, and argues that such division allows Riley to mediate between spiritual dedication to the excursion's object and the tainted 'world' of commerce and bodily needs. It concludes by deploying Peter Larkin's concepts of sufficiency and scarcity to frame Riley's repeated use of dropping, cadential structures at the excursion's end as a return to what Larkin calls the 'basic conditions' of the ordinary, common world. Bathos, withdrawal and coda are rhetorical figures for the abandonment of vantage in favour of a politics of what will suffice: their deployment circumvents the trajectory of accumulative gain that Riley employs the excursion to critique.